Trade Credit and Temporary Employment How Companies Respond to Capital and Labor Market Frictions - Nielen, Sebastian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book presents an empirical investigation into the relationship between companies' short-term response to capital and labor market frictions and performance. Two different kinds of performance measures are considered, namely innovation performance and firm performance. The author focuses on two major topics: first, on the relation between innovation performance and the use of trade credit. Second, on the relation between firm performance and the use of temporary employment. The use of in-depth firm-level data and state-of-the-art microeconometric methods provide the scientific rigor to this important investigation to answer the questions currently being confronted by many companies in different economies.
Introduction -- Product Innovation, Credit Constraints, and Trade Credit: Evidence from a Cross-Country Study -- Product Innovation and Trade Credit Demand and Supply: Evidence from European Countries -- Temporary Agency Work and Firm Competitiveness: Evidence from German manufacturing firms -- Productivity in German manufacturing firms: Does fixed-term employment matter? -- Summary and Future Research.
Keywords: Finance; Personnel management; Econometrics; Industrial organization; Labor economics; Finance; Finance, general; Industrial Organization; Human Resource Management; Labor Economics; Econometrics; Electronic books